CPM574 : Sequential images / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
Sequential Images & Manipulation builds on the concepts and skills learned by students in motion design especially in video technique and it associate. This is a hands-on course, which will include conceptual, aesthetic and techniques of the sequential Images and Manipulation whereby student will understand, implement, execute a motion photography with skillful ability in doing instructional & training program development, commercial video, News and current affairs for interactive video teleconferencing, cable and streaming media on the web.